2012
DOI: 10.1038/mp.2012.130
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional regulation of emotional memory by 5-HT1B receptors involves hippocampal p11

Abstract: Cognitive impairments are common in depression and involve dysfunctional serotonin neurotransmission. The 5-HT1B receptor (5-HT1BR) regulates serotonin transmission, via presynaptic receptors, but can also affect transmitter release at heterosynaptic sites. This study aimed at investigating the roles of the 5-HT1BR, and its adapter protein p11, in emotional memory and object recognition memory processes by the use of p11 knockout (p11KO) mice, a genetic model for aspects of depression-related states. 5-HT1BR a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 51 publications
1
37
0
Order By: Relevance
“…16,17,25 The evoked peaks were reproducible at the 1-min intervals between depolarizations. Results were analyzed offline with the Quanteon FAST Analysis 4.1 software (Quanteon) in conjunction with the calibration reports.…”
Section: Methodsmentioning
confidence: 85%
“…16,17,25 The evoked peaks were reproducible at the 1-min intervals between depolarizations. Results were analyzed offline with the Quanteon FAST Analysis 4.1 software (Quanteon) in conjunction with the calibration reports.…”
Section: Methodsmentioning
confidence: 85%
“…Constitutive p11 KO mice, which lack p11 in the whole brain and body, show a depression-like behavioral phenotype in several well-established models that measure behavioral despair (e.g., forced swim and tail suspension tests) or anhedonia (e.g., sucrose preference test) 2,14 . P11 KO mice also show a deficit in emotional learning, as indicated by impaired performance in the passive avoidance task 26 . In addition to the observed depressive-like phenotype in these tests, constitutive p11 KO mice show reduced responses to antidepressant administration in the forced swim, tail suspension and novelty suppressed feeding tests 2,14,27 .…”
Section: Behaviors In P11 Mouse Modelsmentioning
confidence: 99%
“…Decreased HTR1B activity enhanced locomotor response to cocaine self-administration (Rocha and others 1998) and alcohol consumption (Crabbe and others 1996) in the HTR1B receptor knockout mice while increased HTR1B function reduced cocaine self-administration in rats with HTR1B agonists (Parsons and others 1998). Recent studies indicated HTR1B in migraine medication (Pytliak and others 2011), emotional memory processing via the hippocampus (Eriksson and others 2012), regulation of serotonin transporter activity (Hagan and others 2012), and an altered relationship between childhood aggression and adulthood hostility (Hakulinen and others 2012). HTR1B appeared to differentially modulate cocaine abuse-related behaviors, with a facilitative influence during periods of active drug use in contrast to an inhibitory influence during protracted withdrawal, suggesting value in stage-based cocaine dependence treatment (Pentkowski and others 2012).…”
Section: Introductionmentioning
confidence: 99%